Assessing the direct and spillover effects of shocks to refugee remittances. (September 2019) - Alix-Garcia, Jennifer; Walker, Sarah; Bartlett, Anne
Highlights: We examine the impact of shutting down remittances into Kakuma refugee camp. Refugee consumption did not decrease on average, but did for households affected by the shutdown. The shutdown hurt the host population, especially those with livelihoods linked to the camp. These findings underscore the important relationships between refugee camps and host communities. Abstract: We examine the impact of exogenously shutting down remittances to Kakuma refugee camp in northern Kenya during 2015. We find that the remittance shutdown did not reduce refugee consumption on average. However, it did decrease consumption of households that previously received remittances through the networks that were closed, while simultaneously increasing consumption for those who continued to receive remittances through other mechanisms. The shutdown also resulted in decreases in the probability of consuming a variety of goods by the host population, particularly those with livelihoods linked to the refugee camp. These findings underscore the tight links between refugee camps and surrounding communities, and are a testament to the multiplier effects of remittances.